The Relationship between Gratification of Internet Usage and Negative Behavior among Youth in Malaysia - Toktam Namayandeh Joorabchi; Mehran Samadi (The Journal of Society and Media, 2022)
Youth are significant consumers of internet technologies. Sometimes, adolescents are directly involved in problematic internet usage, such as online gambling and pornography. They are indirectly exposed to some negative behavior, such as alcohol usage, drug usage, internet addiction, and social isolation. This study aims to identify the relationship between six factors of negative behavior and gratification in using the internet among 440 Malaysian youth by collecting data via survey. The theory applied is the uses and gratification theory (U&G). The results revealed no meaningful relationship between the gratification of using the internet and pornography, online gambling, alcohol, and drug usage. However, there was a significant positive relationship between the gratification of internet use, social isolation, and internet addiction.